SP46 Regional anaesthesia in a diabetic patient. (11th August 2022) - Crowe, G; Atterton, B; Louise, Moran EM
Abstract : Diabetes Mellitus is the most common endocrine disorder globally. 1 A diagnosis of diabetes is a risk factor for peri-operative complications however this risk can be mitigated with improved blood glucose control and individualised peri-operative management. There are numerous potential advantages of utilising regional anaesthesia for patients with diabetes. These include a reduction in post-operative nausea and vomiting, avoidance of possible airway complications associated with general anaesthesia and a reduction in opioid use and length of stay. 2 Unfortunately, there are also risks associated with performing regional anaesthesia on the patient with diabetes, especially those with acquired diabetic neuropathy (DN). DN increases the sensitivity of nerves to local anaesthetics and regional anaesthesia blocks can be excessively prolonged, 3 delaying mobilisation. DN also makes nerve stimulation techniques more difficult as nerves are harder to stimulate (often >1.0mA required) which may result in the needle tip being closer to the nerve than perceived. The neurotoxic effects of local anaesthetics, especially with the addition of vasoconstricting adjuvants, are accentuated in DN. Finally, there is an increased risk of peri-neural catheter infection, therefore heightened vigilance is required to recognise this important complication. 4 The decision to perform regional anaesthesia on patients with diabetes should be taken after careful consideration of the risks and benefits. This problem based learning presentation will review the advantages and disadvantages of using regional anaesthesia in diabetic patients. References: Levy N, Lirk P. Regional anaesthesia in patients with diabetes. Anaesthesia 2021;76 (Suppl. 1):127–135. Ulka CM, Shotwell MS, Gupta RK, Sandberg WS, Ehrenfeld JM. Regional anesthesia, time to hospital discharge, and in-hospital mortality: a propensity score matched analysis. Regional Anesthesia and Pain Medicine 2014;39 :381–6. Cuvillon P, Reubrecht V, Zoric L, et al . Comparison of subgluteal sciatic nerve block duration in type 2 diabetic and non-diabetic patients. British Journal of Anaesthesia 2013;110 :823–30. Nicolotti D, Iotti E, Fanelli G, Compagnone C. Perineuralcatheter infection: a systematic review of the literature. Journal of Clinical Anesthesia 2016;35 :123–8.